2017
DOI: 10.1007/978-1-4939-6875-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cholesterol Transfer from Lysosome to Peroxisome Using an In Vitro Reconstitution Assay

Abstract: Low-density lipoproteins (LDLs) are taken up by the cell mainly through receptor-mediated endocytosis. LDL-derived cholesterol leaves lysosome and further transports to downstream organelles for specific cellular needs. We recently report that cholesterol transfers from lysosome to peroxisome through lysosome-peroxisome membrane contact (LPMC). Here, we use iodixanol density gradient centrifugation to isolate lysosomes and peroxisomes separately for the in vitro reconstitution of LPMC. We also apply H-choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In 2015, the Bao-Liang Song research group demonstrated that cholesterol transport is abnormal in ALD fibroblasts and in the Abcd1 mouse model for ALD as well as in other peroxisomal disorders. Low-density lipoprotein (LDL)-derived cholesterol was transported from the lysosome to the peroxisome in a manner that depended upon lysosomal synaptotagmin VII binding to the peroxisomal lipid phosphatidylinositol 4, 5-bisphosphate [PI(4,5)P 2 ] on the peroxisomal membrane (Chu et al, 2015;Hu et al, 2018;Islinger, Voelkl, Fahimi, & Schrader, 2018;Jin, Strunk, & Weisman, 2015;Luo, Jiang, Yang, & Song, 2018;Luo, Liao, Xiao, & Song, 2017;Stefan et al, 2017). While these findings were initially called into question by van Veldhoven et al in a letter to the editor (van Veldhoven, Baes, & Fransen, 2015), correctly identifying an error in Chu et al's method, a recent follow-up publication (Xiao et al, 2019) validates the initial Chu et al (2015) findings.…”
Section: Cholesterol Transport In Aldmentioning
confidence: 99%
“…In 2015, the Bao-Liang Song research group demonstrated that cholesterol transport is abnormal in ALD fibroblasts and in the Abcd1 mouse model for ALD as well as in other peroxisomal disorders. Low-density lipoprotein (LDL)-derived cholesterol was transported from the lysosome to the peroxisome in a manner that depended upon lysosomal synaptotagmin VII binding to the peroxisomal lipid phosphatidylinositol 4, 5-bisphosphate [PI(4,5)P 2 ] on the peroxisomal membrane (Chu et al, 2015;Hu et al, 2018;Islinger, Voelkl, Fahimi, & Schrader, 2018;Jin, Strunk, & Weisman, 2015;Luo, Jiang, Yang, & Song, 2018;Luo, Liao, Xiao, & Song, 2017;Stefan et al, 2017). While these findings were initially called into question by van Veldhoven et al in a letter to the editor (van Veldhoven, Baes, & Fransen, 2015), correctly identifying an error in Chu et al's method, a recent follow-up publication (Xiao et al, 2019) validates the initial Chu et al (2015) findings.…”
Section: Cholesterol Transport In Aldmentioning
confidence: 99%
“…Cholesterol is synthesized de novo by a pathway shared by the ER, mitochondria and the cytosol, or taken up by food consumption where it is delivered to the target cells via LDL, which under normal conditions is the dominant route of cellular cholesterol supply. After LDL uptake by plasma membrane LDL receptors, LDL‐contained lipids are transported via endosomes to lysosomes, where cholesterol is liberated by acid lipase from the cholesteryl esters and targeted to the ER for redistribution into the different subcellular membranes . Unexpectedly, knockdown of a considerable number of peroxisomal genes led to the accumulation of cholesterol in lysosomes indicating that peroxisomes might be involved in this cellular cholesterol transport system .…”
Section: Peroxisome‐lysosome Contacts and Cholesterol Traffickingmentioning
confidence: 99%
“…Proteins which actively deliver cholesterol from lysosomes to peroxisomes have not yet been identified. Specific StAR‐related lipid transfer (START) domain proteins (STARDs), OSBPs, and OSRPs may be involved in this nonvesicular trafficking pathway . While such molecular details have still to be revealed, a recent follow‐up study by the Song‐group reports novel insights into the regulatory mechanism which could facilitate dynamic interactions of peroxisomes and lysosomes at the LPMCs .…”
Section: Peroxisome‐lysosome Contacts and Cholesterol Traffickingmentioning
confidence: 99%